2018
DOI: 10.1038/s41598-018-19376-0
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel materials for additive manufacturing - Isotropic microstructure and high defect tolerance

Abstract: Electron Beam Melting (EBM) is a powder-bed additive manufacturing technology enabling the production of complex metallic parts with generally good mechanical properties. However, the performance of powder-bed based additively manufactured materials is governed by multiple factors that are difficult to control. Alloys that solidify in cubic crystal structures are usually affected by strong anisotropy due to the formation of columnar grains of preferred orientation. Moreover, processing induced defects and poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
78
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 70 publications
13
78
0
1
Order By: Relevance
“…It was shown that the material in its as-built condition, i.e., without the necessity of elaborate post-processing, is capable of addressing the aforementioned major current challenges in powder bed-based AM. 35 Firstly, independent of the applied process parameters, the steel is characterized by a homogeneous microstructure with a remarkably weak texture, i.e., approximately 1.6 and 1.4 multiples of uniform distribution (MUD) as determined by electron back-scatter diffraction (EBSD) and x-ray diffraction (XRD). Moreover, relatively fine grains prevail with a mean areaweighted grain size of approximately 20 lm, as derived from EBSD data (cf.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the material in its as-built condition, i.e., without the necessity of elaborate post-processing, is capable of addressing the aforementioned major current challenges in powder bed-based AM. 35 Firstly, independent of the applied process parameters, the steel is characterized by a homogeneous microstructure with a remarkably weak texture, i.e., approximately 1.6 and 1.4 multiples of uniform distribution (MUD) as determined by electron back-scatter diffraction (EBSD) and x-ray diffraction (XRD). Moreover, relatively fine grains prevail with a mean areaweighted grain size of approximately 20 lm, as derived from EBSD data (cf.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some limitations and problems that need to be considered and addressed when using AM, dimensional accuracy [16,17], process and geometric repeatability [18][19][20], and material defects [21][22][23] being the primary considerations. While all are important considerations, the most essential from the perspective of engineering design are the dimensional accuracy and repeatability of the final parts.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some limitations and problems that need to be considered and addressed when using AM, dimensional accuracy [13,14], process and geometric repeatability [15][16][17], and material defects [18][19][20] being the primary considerations. While all of these are important to examine, the most important from the perspective of engineering design are the dimensional accuracy and repeatability of the final parts.…”
Section: Of 27mentioning
confidence: 99%